2022
DOI: 10.3390/biomedicines10020453
|View full text |Cite
|
Sign up to set email alerts
|

The Concept of Indeterminable NASH Inducted by Preoperative Diet and Metabolic Surgery: Analyses of Histopathological and Clinical Features

Abstract: Practitioners routinely perform intraoperative liver biopsies during laparoscopic sleeve gastrectomy (LSG) to evaluate nonalcoholic fatty liver disease (NAFLD). In some patients, hepatocyte ballooning, inflammation, and fibrosis without steatosis are observed, even in the absence of other etiologies. We call this finding indeterminable nonalcoholic steatohepatitis (Ind-NASH). In this study, we clarified the prevalence, as well as histopathological and clinical features, of Ind-NASH through intraoperative liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…As we previously reported, LSG dramatically improves not only the clinical parameters related to NAFLD but also liver fibrosis, as assessed using the pericellular fibrosis score (PFS), a central vein fibrosis index [4]. In addition, though time-consuming, we also reported that fibrosis of NASH was improved by MS and resulted in a return to normal liver function [1]. Thus, expanding the indications for MS further is a desirable goal of future research.…”
mentioning
confidence: 73%
See 3 more Smart Citations
“…As we previously reported, LSG dramatically improves not only the clinical parameters related to NAFLD but also liver fibrosis, as assessed using the pericellular fibrosis score (PFS), a central vein fibrosis index [4]. In addition, though time-consuming, we also reported that fibrosis of NASH was improved by MS and resulted in a return to normal liver function [1]. Thus, expanding the indications for MS further is a desirable goal of future research.…”
mentioning
confidence: 73%
“…Three groups were compared according to the NAS or PFS using one-way analysis of variance with Tukey's post hoc test. Univariate and multivariate analyses with a linear regression model were conducted to analyze predictive factors associated with NAS and PFS; the variables were selected based on the results of univariate analysis and previous reports [1,4]. All statistical analyses were performed using the EZR software version 1.61 (Jichi Medical University, Saitama Medical Center, Saitama, Japan) [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…NAFLD subtypes include nonalcoholic fatty liver (NAFL) and nonalcoholic steatohepatitis (NASH), with NASH patients who suffer from advanced fibrosis being at increased risk of liver cirrhosis and liver disease-related death [ 2 ]. Metabolic surgery (MS), including laparoscopic sleeve gastrectomy (LSG), dramatically improved histological findings of NASH as well as type 2 diabetes (T2D); therefore, LSG and other MS may be strong alternatives for improving NASH [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%